Basic atomic and molecular spectroscopy - Hollas, J. Michael (London Royal Society of Chemistry, 2002)
The main aim of this unique book is to introduce the student to spectroscopy in a clear manner which avoids, as far as possible, the mathematical aspects of the subject. It is thus intended for first or second year undergraduates, particularly those with minimal mathematics qualifications. After explaining the theory behind spectroscopy, the book then goes on to look at the different techniques, such as rotational, vibrational and electronic spectroscopy. It encompasses both high resolution (structural) and low resolution (analytical) spectroscopy, demonstrating their close interrelationship. The many worked problems make this book particularly appealing for independent study. Ideal for the needs of undergraduate chemistry students, Tutorial Chemistry Texts is a major new series consisting of short, single topic or modular texts concentrating on the fundamental areas of chemistry taught in undergraduate science courses. Each book provides a concise account of the basic principles underlying a given subject, embodying an independent-learning philosophy and including worked examples.